Out of policymaker’s sight: the role of banks’ liquidity preference in credit supply in Brazil - Fernanda Ultremare; Olívia Bullio Mattos (Revue de la Régulation)
In modern, sophisticated banking systems, in addition to endogenously creating money, banks have the ability to innovate and stretch constraints on their portfolio to potentially raise profits. They fulfill demand for credit according to their liquidity preference and expectations of profits. On the other hand, the monetary authority influences credit supply by changing the availability of liquid assets compared to other assets through monetary policy instruments. By managing liquidity in the reserves market, central banks modify the price of access to short-term liquidity – the interest rate – and, thereby, cause changes in the yield curve and transform banks’ propensity to expand credit. Even though determining credit supply is a difficult task since it depends on expectations and cannot be calculated in advance, this paper aims to determine a credit supply function for Brazil. Our empirical strategy was to estimate a dynamic panel data model on a large cross-section bank-level dataset from the Brazilian Central Bank using balance sheet information from the fifty largest banks operating in the country from 1999 to 2016. Credit outstanding was matched with time-varying indicators that were prepared using data from banks’ portfolios and then combined with macroeconomic variables. We use a Post-Keynesian framework to analyze the relation between credit supply and the balance sheet composition of banks. Our findings suggest that variations in banks’ liquidity preference which are reflected on their changes in flexibility and leverage indicators have a significant impact on credit supply in Brazil.JEL codes: E51, E52, E47